Attitudes towards invisible disabilities: Evidence from behavioral tendencies - Marine Granjon; Nicolas Pillaud; Maria Popa-Roch; Benoite Aubé; Odile Rohmer (Current Research in Behavioral Sciences)
Invisible disabilities account for 70–80 % of all disabilities yet are often overlooked in social psychology research. Despite their prevalence, these conditions are frequently misunderstood and less recognized, leading to potential biases and negative perceptions. This research aims to address a critical knowledge gap by investigating attitudes toward invisible disability. We hypothesize that attitudes toward invisible disabilities are more negative than toward visible disabilities. Using an immersive behavioral tendency paradigm, the VAAST (Visual Approach/Avoidance by the Self Task), we were able to observe participants' approach/avoidance reactions in a simulated environment. Three studies (Ntotal = 444) were conducted. Studies 1 and 2 compared approach-avoidance tendencies towards visible and invisible disabilities, the former in the general population and the latter within a population of teachers. Study 3 used a variation of this paradigm, the Incidental-VAAST, to address control bias. Results, supported by multi-level frequentist and Bayesian statistics, as well as a mini meta-analysis, indicated consistently stronger negative attitudes towards invisible disabilities. By showing that individuals with invisible disabilities face greater prejudice than those with visible disabilities, this research advances our understanding of how visibility impacts social bias, adding depth to theories of prejudice.